Room Air Purification through the “Silent Virus Killer” - R. Asfar , Khaled; M. Sawan, Saifeddin (Journal of Ecohumanism, 2024)
A “Silent Virus Killer” is proposed for room air purification/sanitization. This unit is primarily an indoor space heater in winter time in many homes around the world as kerosene or gas heaters. The proposed outcome of these heaters, in addition to warming room air with high thermal efficiency, is thought to annihilate airborne viruses, bacteria, and living organisms inside rooms, classrooms, or businesses. These airborne micro-organisms are completely eliminated by incineration when the air carrying these tiny creatures passes through the high-temperature glowing dome space heaters. Kerosene and LPG gas burn at temperatures above 900o C. No living organisms can survive these temperatures. The Corona virus and all other viruses cannot survive temperatures above 70oC. The driving force that moves the heated air upwards above the heater and draws cold air from below the heater is due to buoyancy. Rising hot air column cools down when it mixes with the room colder air and eventually impinges the much colder ceiling. Consequently, it diverges radially outward from the point of impingement with the ceiling and goes down towards the floor. The current study consists of two parts; Numerical simulation of the flow field due to this phenomenon as well as an experimental part which measures temperature and velocity distribution in the rising hot air column. The numerical simulation is carried out using the XFLOW Code. Several combustion temperatures are assumed at the outlet of the glowing dome in the heater ranging from 600-900 degrees Celsius. Temperatures and rising hot air column upward velocities are obtained. The experimental part is also carried out on a kerosene heater and its effect on purifying/sanitizing the room air is studied. The location of the heater in a given room size is investigated and an optimum position is determined. Room ventilation is a necessity for such heaters.